Aligning visual imagery to the operator improves geospatial situation awareness in a single-display 360-degree periscope concept - Jason Bell; Zachary Howard; Stephen Pond; Troy Visser; Madison Fitzgerald; Megan Schmitt; Shayne Loft; Steph Michailovs (Cognitive Research, 2025)
Abstract Technological advances mean that it is now possible to represent the entire 360° view of the horizon to a submarine periscope operator simultaneously, in strips on a single display, as opposed to the restricted view offered through a conventional periscope aperture. Initial research showing performance improvements for such panoramic displays is promising. However, that research has yet to consider the importance of alignment between the visual representation of the environment on the periscope display and the operator themselves (i.e. the visual field compatibility principle). Using a simulated periscope operator task, the current study assessed whether the degree of display-operator alignment influences periscope operator geospatial situation awareness (SA). Four increasingly misaligned display configurations and three different operator orientations (relative to simulated Ownship travel) were assessed. Trained novices (N = 83) were tasked with judging the position of contacts on their display by pointing a joystick at their “real-world” location to measure geospatial SA. Results revealed a strong influence of display-operator alignment on geospatial SA: an aligned display representing contacts in front of an operator at the top of the display and contacts behind an operator at the bottom of the display, produced better geospatial SA (faster, more accurate responses) than other, less aligned display configurations. Diffusion modelling indicated that greater display alignment improved geospatial SA by both increasing information-processing speed and decreasing the amount of evidence required to make decisions. We conclude that geospatial SA can be facilitated by panoramic designs that maximise the alignment of the display to the external world.